University of the World: A Case for a World University System - Lenzen, Dieter (Springer, 2016)
In this book, Dieter Lenzen analyzes the world's three major educational systems: the Continental-European, the Atlantic (Anglo-American) and the East Asian. Distancing himself from the current trend towards the economically driven Anglo-American system of education, the author proposes an alternative model, "a university of the world".